1986
DOI: 10.1111/j.1550-7408.1986.tb05604.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Studies of Blastocrithidia triatomae (Trypanosomatidae) in the Rectum of Triatoma infestans (Reduviidae)12

Abstract: ABSTRACT. The morphology of Blastocrithidia triatomae, when colonizing the rectum of Triatoma infestans, was studied by scanning electron microscopy. The posterior end of the epimastigote's body is tapered and often rolled up. The “straphangers” (cyst stages) are connected with the flagellum by “cytoplasmic bridges”; after “straphanger” detachment these bridges persist as remnants. A comparison of colonization densities of B. triatomae and Trypanosoma cruzi shows that both prefer to colonize the rectal gland,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…We did not observe the "cytoplasmatic bridge" mentioned by Schaub and Böker (1986) in their microscopic studies of B. triatomae, nor were we able to find cysts connected to the posterior end of epimastigotes as reported by the authors in three cases.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We did not observe the "cytoplasmatic bridge" mentioned by Schaub and Böker (1986) in their microscopic studies of B. triatomae, nor were we able to find cysts connected to the posterior end of epimastigotes as reported by the authors in three cases.…”
Section: Discussioncontrasting
confidence: 62%
“…In B. cyrtomeni, it was observed as needle-like in light SEM and TEM images (Figs 1B,13). In contrast, Schaub and Böker (1986) observed that the broad posterior end was rolled up in a spiral in the first SEM images of B. triatomae and B. gerridis.…”
Section: Discussionmentioning
confidence: 83%
“…First instar larvae of Triatoma infestans were infected in vitro with Blastocrithidia triatomae, using a mixture of cryopreserved cysts from in vitro cultures of the original strain and mouse blood (300,000 cysts/ml blood; Schaub and Bo¨ker 1986a). Bugs were then fed on hens 5, 6, 9 and 10 weeks p.i., getting their last feed 14 weeks p.i.…”
Section: Methodsmentioning
confidence: 99%
“…For disinfection of the eggs deposited in each group the method of Geering-Sacher [ 131 was adapted, using Desogenm (Ciba Geigy, Basle, Switzerland) and Chloramin T (Serva, Heidelberg, FRG). We also used a similar procedure for disinfection of suspensions of B. triatomaecysts [32]. Since it killed all bacterial contaminations but only about 90% of the cysts, we discarded those eggs which were visibly contaminated with feces.…”
Section: Methodsmentioning
confidence: 99%